A Causal AI Suite for Decision-Making - Kiciman, Emre; Dillon, Eleanor; Edge, Darren; Foster, Adam; Hilmkil, Agrin; Jennings, Joel; Ma, Chao; Ness, Robert Osazuwa; Pawlowski, Nick; Sharma, Amit; Zhang, Cheng (NeurIPS 2022 Workshop on Causality for Real-world Impact, 2022)
Critical data science and decision-making questions across a wide variety of domains are fundamentally causal questions. We present a suite of open-source causal tools and libraries that aims to simultaneously provide core causal AI functionality to practitioners and create a platform for research advances to be rapidly deployed. In this paper, we describe our contributions towards such a comprehensive causal AI suite of tools and libraries, its design, and lessons we are learning from its growing adoption. We hope that our work accelerates use-inspired basic research for improvement of causal AI.